Moral Principles in Multicultural Hadith Studies - Nurul Qomariyah; Damanhuri (al-Afkar, Journal For Islamic Studies, 2024)
Writing a manuscript with the title: Moral Principles in multicultural hadist study, aims to find out and understand the quality of  hadist and fiqhul hadist using a study library research approach. The problem formulation is (1). How to analyze the quality of multicultural hadist in moral principles. (2). How to analyze the concept of multicultural hadist fiqhul in moral principles. The benchmarks for the quality of society in achieving mature moral awarness, to achieve awarness of moral principles include: first the principle of good attitudes, namely by positioning the willigness to see other people as dignified individuals. Second, the principle of justice is a strong and constant will to give everyone what is their right, based on the principle of justice which is in the same situation, for exampel helping fellow humans in need. Third, respect yourself by being honest, polite, humble, patient, simple, tolerant, willing to take responsibility, and appreciative.